Awareness of Breast Cancer, Attitude and Practice towards its Screening among Female Support Staff - Thapa, Savina; Awale, Shanti; Shrestha, Sharmila (Journal of Karnali Academy of Health Sciences, 2021)
Background: Breast cancer is the most common cancer among women worldwide. In developing countries, mortality from breast cancer is higher than in developed countries due to low levels of knowledge and poor practice of breast cancer screening. This study aims to assess the awareness of breast cancer, attitude, and practice of its screening among female support staff. Method: A cross-sectional study was conducted at Patan Academy of Health Sciences using a structured questionnaire. One hundred and twenty-seven female support staff was interviewed. Descriptive statistics such as frequency and percentage were used to analyze the level of awareness, attitude, and practice. The relationship between awareness and practice, attitude and practice were analyzed using Spearman’s correlation co-efficient. Results: The majority of respondents had a poor level of awareness regarding breast cancer and screening (64.57%: poor level, 28.35%: average level, and 7.14%: good level). Over half of the respondents (52.76%) reported a favorable attitude towards breast cancer screening practice and 37% of respondents had performed breast cancer screening methods. There was a significant mild correlation (r =.313, p = .032) between awareness and practice, whereas there was no significant correlation (r = -.045, p= .726) between attitude and practice. Conclusion: Overall, the majority of female support workers interviewed had poor awareness of breast cancer and screening. The potential impact is that fewer women are encouraged to take up these services and may therefore be at risk of developing breast cancer.